Sejarah Pesantren dan Tradisi Keilmuannya di Jawa - Ahmad Misbah; Bahru Rozi (Al-Jadwa: Jurnal Studi Islam, 2022)
Islamic boarding schools are the oldest educational institutions that still adhere to Islamic traditions which in their establishment aim to explore and practice Islamic teachings as a guideline for life and daily behavior. The aims of this study were (1) to know the overall picture of the early history of the establishment of Islamic boarding schools in Java (2) to know the scientific traditions of Islamic boarding schools in Java. This study uses library research methods (library research). The results of this study indicate that: (1). The founders of Islamic boarding schools in Java based on their periodization are: Initial period: Shaykh Mawlana Malik Ibrahim, Sunan Ampel, Sunan Giri, Raden Fatah, Sultan Trenggono, Fatahillah. Period 17-18 AD: Sultan Agung, Maulana Yusuf, Ki Jatira. 19-20 Century Period AD: KH. A. Hasyim Asy'ari, KH. Abdul Wahhab Hasbullah. (2) The scientific tradition of Islamic boarding schools in Java originates from Wali Songo's understanding and interpretation of Islamic